Effect of different ions on dissolution rates of silica and feldspars at high pH. (February 2022) - Bagheri, M.; Lothenbach, B.; Shakoorioskooie, M.; Scrivener, K.
Abstract: The dissolution kinetics of silica-containing minerals in aggregates influences strongly the process of ASR in concrete. In this paper, the effect of different ions on the dissolution rates of SiO2 (amorphous and quartz) and feldspars at high pH values was studied by following the increase of silicon concentrations in dissolution experiments and with a novel approach of measuring the evolution of scratches of polished surfaces. The second method avoided the problem of precipitation in some systems, such as the formation of C-S-H when calcium was present and lithium silicates in the presence of lithium. At high pH values, lithium, calcium and sulfate increased the dissolution rates of silica and feldspars, while iron, magnesium and additional NaCl, KCl or CsCl showed no significant effect. In contrast, aluminium slowed down significantly the dissolution rates of quartz, amorphous silica and Na and K-feldspar at for all temperatures studies: 20, 40 and 60 °C.